Spesies Hemiptera pada Tanaman Kangkung (Ipomoea aquatica) di Kabupaten Ogan Ilir, Sumatera Selatan - Novhela, Shelly; Liana, Liana; Febriani, Bella; Mubarok, Zaki; Zahir, M Ibrahim; Umayah, Abu; Gunawan, Bambang; Arsi, Arsi (Seminar Nasional Lahan Suboptimal, 2022)
Novhela S, Liana L, Febriani B, Mubarok Z, Zahir MI, Umayah A, Gunawan B, Arsi A. 2022. Hemiptera species on water spinach (Ipomoea aquatica) in Ogan Ilir Regency, South Sumatra. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 742-750. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Hemiptera species are insects that often found in water spinach (Ipomoea aquatica). The purpose of this study is to knowing the diversity of Hemiptera species in water spinach. This research method was carried out by field surveys in Timbangan Village, Sakatiga Village, and Tanjung Pering Village, Ogan Ilir Regency, South Sumatra. Data from the research on the diversity of Hemiptera insects on water spinach (Ipomoea aquatica) were analyzed descriptively. The results showed that there were four Hemiptera species found in water spinach. The four Hemiptera species include Anasa Tritis (true ladybug), Bothrogonia ferruginea (pucung father), Boisea trivitta,  and Gonocerus akutangulatus (box bugs). Based on the four species, three of them are insects that act as phytophages in the ecosystem of life, especially in the agricultural sector. While one other species is an insect that acts as a predator (natural enemy). So, the insects that are often found in water spinach plants (Ipomoea aquatica) are Hemiptera species insects that act as phytophagoes and predators. Suggestions that can be given from the results of this study are the need for more education and understanding of the community about the various Hemiptera species that found in water spinach, especially those that are pests in the villages of Scales, Sakatiga, and Tanjung Pering, Ogan Ilir Regency, South Sumatra.